Pre-hospital emergency medicine and the trauma intensive care unit. (August 2019) - Frostick, Emily; Johnson, Christopher
The system of trauma care has been revolutionised over the last decade with the introduction of major trauma networks across the United Kingdom and the development of subspecialist national training in pre-hospital emergency medicine. Pre-hospital care providers feed trauma patients into trauma units or major trauma centres depending upon the severity of their injuries and their stability for a potentially longer primary transfer to access specialist major trauma services. Trauma services are continually adapting and improving with the introduction of more advanced techniques into the pre-hospital arena are on the horizon, enabling trauma patients to receive more specialised treatment from medical professionals earlier after injury; this article will discuss some of the recent developments within pre-hospital emergency medicine, in-hospital trauma care and on into the intensive care unit, and how this has led to improved outcomes.